Analisis Penerapan Sistem Manajemen Mutu UPT Pusat Bahasa untuk Mencapai Kepuasan Pengguna (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
Unesa Language Center is a supporting organization that supports language services at the State University of Surabaya, which focuses on the field of service and ins the quality of students and graduates to have traditional foreign language skills. Language Center takes a policy to carry out the development of the organization as one of the preventive efforts of the demands of the community by committing to carrying out continuous improvement through the implementation of the Quality Management System (QMS) International Standard Organization (ISO) 9001: 2015. This research is carried out through a qualitative approach to find the problem of applying existing quality management. The focus of this study includes changing organizational culture, adapting business processes, and strengthening the quality of administrative services. The implementation of quality management is carried out by preparing changes in the culture of the organization bringing and controlling the application of quality culture, the adaptation of the business processes of quality management, as well using the organization’s activities by implementing SOP to maintain and improve the quality of application of the management of quality.